Book Review The semiotics of new spaces: Languaging and literacy practices in one South African Township – Charlyn Dyers - Coetzee, Frieda (Multilingual Margins: A journal of multilingualism from the periphery, 2023)
Charlyn Dyers’s, The semiotics of new spaces: Languaging and literacy practices in one South African township (2018) provides a rich description and analysis of the language and literacy practices in a township called Wesbank – situated on the socio-economically peripheral margins of the city of Cape Town.